2016
DOI: 10.1007/s10943-016-0301-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Sense of Coherence and Mindfulness in an Ecclesiastical, Intercultural Group Training Context

Abstract: Sense of coherence (SOC) and mindfulness (MI) are believed to promote the health and well-being of individuals and organisations. The aim of this longitudinal study was to contribute to the literature on the development of SOC through training and interventions and thereby explore the development of these constructs in a group of senior professionals in the German Catholic Church. A sample of eight participants voluntarily enrolled for a 12-day training programme spread over a period of nine months to develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 58 publications
1
0
0
Order By: Relevance
“…The current study concluded that compassion-focused therapy is effective in improving feelings of coherence, as supported by other studies [22], [31], [39], which indicated that the sense of coherence can be enhanced through various therapeutic approaches. Compassion-focused therapy is an effective approach to enhancing self-compassion and personal agency among university students, as well as to improving psychological well-being [13].…”
Section: Discussionsupporting
confidence: 84%
“…The current study concluded that compassion-focused therapy is effective in improving feelings of coherence, as supported by other studies [22], [31], [39], which indicated that the sense of coherence can be enhanced through various therapeutic approaches. Compassion-focused therapy is an effective approach to enhancing self-compassion and personal agency among university students, as well as to improving psychological well-being [13].…”
Section: Discussionsupporting
confidence: 84%